Doctor Decision-Making and Patient Outcomes - Currie, Janet; MacLeod, W. Bentley; Musen, Kate (Journal of Economic Literature, 2026)
Doctors often treat similar patients differently, which affects health outcomes and medical spending. We assess the recent literature on doctor decision-making through the lens of a model that incorporates diagnostic and procedural skills, beliefs, incentives, and differences in patient pools. Decision-making is affected by beliefs, training, experience, peer effects, financial incentives, and time constraints. Interventions to improve decision-making include providing information, guidelines, and technologies like electronic medical records and algorithmic decision tools. Economists have made progress in understanding doctor decision-making, but applications of that knowledge to improving health care are still limited. (JEL D83, D91, G51, I11, I14, J24, J44)